MENENTUKAN WAKTU PROSES PRODUKSI PRODUK BEJANA TEKAN DENGAN METODA MULTIPLE REGRESI LINEAR - Nyoman G Suryadharma (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2015)
Pressure vessel is a kind of plant equipment, which has a wide fuction to support the industrial process. The increasing of economic growth, causing the increasing demand of industrial equipment including pressure vessel. Therefore to have competitive advantage in global market, a just in time production cost calculation of pressure vessel are the most important matter. One of the faktor which have a significant effect in the calculation of cost is the requirement of operation time or man hour, because calculation of operation time is more accurate to reduce either losses or error in the prediction of delivery time. The study, analyze the purposes to get of the operation time planning on the pressure vessel’s main element. This has been done by production modeling with a multiple linear regression at least square method, and the result of linearization become a basic parameter to calculate the estimate of manufacturing cost. The equation for the modeling system is: Y1,..n= f( X1, X2, …. Xn). Where : Yi is the operation each an operation process such as marking, cutting, welding and others. Xi is each dimension parts the pressure vessel such as thickness, Outside diameter and others. This analyze can get a estimate the operation time closer the actual operation time